Rancang Bangun Sistem Informasi Vaksinasi Pada Balita Menggunakan Metode Waterfall - Yuli Syafitri (Jurnal Teknologi dan Informatika (JEDA), 2021)
AbstractIntegrated Service Post or Posyandu is a form of Community-Based Health Efforts (UKBM) carried out by, from and with the community, to empower and provide facilities for the community to obtain health services for mothers, babies and toddlers. However, one of the main problems in the integrated service post is still implementing non-computerized data processing and information dissemination so that the process flow is still recording the attendance list of infants and toddlers, recording immunization data, and recording the weight of infants and toddlers in the form of a health book. Mother and Child (KIA) or recording on paper. This causes several obstacles, namely processing administrative data which takes time, and recording books that are easily lost or damaged or sometimes forgotten books are taken during posyandu activities. Besides that, another problem is the process of searching for data one by one, so it takes a long time. In line with the convenience to the community, the authors propose a Web-based information system for toddlers vaccine data collection at Posyandu as an effort to facilitate information. The toddler vaccine data collection system at the posyandu can help to simplify the process of vaccine data collection and data processing for toddlers at the posyandu and also for posyandu officers to carry out the input process to process data that is good, precise and fast.